Analysis Of The Effect Of Loading On Parallel Generator Work At PT. Mitrabara Adiperdana Tbk - Sartika, Linda; Prasetia, Abdul Muis; Mado, Ismit; Fidarwati (Muhammadiyah University, Sidoarjo, 2023)
Genset is a combination of two different devices: the engine as a rotating device and the generator as a generating device. Genset at PT. Mitrabara Adiperdana. Tbk is used as a backup when the electricity source from PLN goes out. Due to fluctuating loads, an ample power supply is needed when the conveyor is operating, so more than one generator is needed to supply electricity according to load demand. To meet the power needs at PT. Mitrabara Adiperdana. Tbk, 2 gensets with a capacity of 500 kVA and 3 gensets with a capacity of 800 kVA were synchronize. Generator synchronization aims to obtain optimal power, good efficiency and efficient specific fuel consumtion (SFC). When 5 generator units were paralleled, the lowest efficiency was 19.2% with an SFC of 0.48 liters/kWh in September with a capacity of 800 kVA, while the highest efficiency was 62.98% with an SFC of 0.15 liters/kWh in July with a capacity of 800 kVA. The calculation result, when given the same loading, obtained the lowest efficiency of 1% with an SFC of 9.3 liters/kWh in August with a capacity of 500 kVA and the highest efficiency of 51.45% with an SFC of 0.18 liters/kWh in August with a capacity og 800 kVA. The calculation result show that the efficiency is affected by the amount of output power, the difference in the initial year of operation, anf the difference in several parameters of the nmaplate. Meanwhile, the generator’s Specific Fuel Consumtion (SFC) is influenced by the output and hours meter.